2020
DOI: 10.1111/geb.13107
|View full text |Cite
|
Sign up to set email alerts
|

Negative effects of urbanization on terrestrial arthropod communities: A meta‐analysis

Abstract: Aim Urbanization is one of the most significant anthropogenic alterations of the surface of the Earth and constitutes a major threat to biodiversity at the global level. Arthropods are a very diverse group of organisms, with many species that provide essential ecosystem services. However, their response to urbanization is still unclear. Here, we describe the first meta‐analysis to evaluate the overall effects of urbanization on terrestrial arthropod communities and driving factors related to cities, arthropods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
193
3
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(224 citation statements)
references
References 95 publications
24
193
3
4
Order By: Relevance
“…The estimated effect of urban areas was still negative after accounting for potential stops during sampling ( Figure 4). Our results are consistent with a recent meta-analysis combining data from multiple studies to show an overall negative effect of urbanisation for arthropod diversity and abundance (Fenoglio, Rossetti & Videla, 2020) and the decline of insect diversity with urbanisation at multiple spatial scales (Piano et al, 2020). In large part, this may be due to the reduced biomass and productivity per unit area in urban habitats where much of the landscape is impervious surface, such as cement or rooftops, on which vegetation does not grow.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The estimated effect of urban areas was still negative after accounting for potential stops during sampling ( Figure 4). Our results are consistent with a recent meta-analysis combining data from multiple studies to show an overall negative effect of urbanisation for arthropod diversity and abundance (Fenoglio, Rossetti & Videla, 2020) and the decline of insect diversity with urbanisation at multiple spatial scales (Piano et al, 2020). In large part, this may be due to the reduced biomass and productivity per unit area in urban habitats where much of the landscape is impervious surface, such as cement or rooftops, on which vegetation does not grow.…”
Section: Discussionsupporting
confidence: 91%
“…Across several insect taxa, Piano et al (2020) found that urbanisation was associated with a decline in insect diversity at multiple spatial scales in Belgium. Similarly, a recent meta-analysis combining studies from across the world found a mean negative effect of urbanisation on terrestrial arthropod diversity and abundance, although the effect may differ among insect orders (Fenoglio, Rossetti & Videla, 2020). Long-term monitoring in Britain found lepidopteran biomass to be lower in urban sites compared to woodland and grassland (Macgregor et al, 2019).…”
Section: The Effect Of Urbanisation On Insect Diversity and Biomassmentioning
confidence: 96%
“…Similarly, there is mounting evidence that light pollution is driving local declines in suburban and urban locations (45,46). Although not an emphasis of the 11 articles, urbanization is increasingly recognized as an important stressor (47,48).…”
Section: What's In This Special Issue?mentioning
confidence: 99%
“…Furthermore, urban expansion exaggerates urban heat island effects, causing temperatures in urban areas to be up to 10 °C–12 °C higher than those in the surrounding rural areas 1 , 2 . Therefore, urban habitats, with their impervious asphalt roads and buildings, are often considered disturbed habitats, hostile to arthropod survival 3 .…”
Section: Introductionmentioning
confidence: 99%